Development and evaluation of a cosmetic cream formulation containing annona muricata leaves extract - Omar, Nur Ain; Abd Razak, Fashli Syafiq; Tang, Cher Hing; Helal Uddin, A.B.M.; Sarker, Md Zaidul Islam; Janakiraman, Ashok Kumar; Liew, Kai Bin (Colegio de Farmaceuticos de la Provincia de Buenos Aires, 2021)
Cosmetics are being widely used globally for both woman and man. Annona muricata extract has strong anti-oxidant activity. Antioxidants can reduce the signs of aging and are known as antiaging and anti-wrinkles. The aim of the present study was to formulate and optimize a best formulation of the cosmetic cream containing Annona muricata leaves extract. The blank cream was prepared using various types of emulsifiers at various concentrations. The aqueous phase and oily phase were heated up separately by using water bath at 70 °C and mixed until homogenous. The blank cream was evaluated for their physical properties and stability. When methyl paraben was being substituted with benzyl alcohol, no bacterial growth was observed. The fulfillment of choosing the best formulation was based on the evaluations of microbial and physical stability. Cream 8 was the best formulation of the blank cream due to the fullfillment of the parameters of the evaluations. The formula of cream 8 was added with 2%, 5% and 10% of A. muricata leaves extract. The A. muricata cream was physically stable and showed anti-oxidant activity. The final product of A. muricata cosmetic cream can be a potential antioxidant cosmetic cream to be marketed in the future.